PENGARUH GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN - Netania Emilisa (Media Riset Bisnis & Manajemen, 2006)
The general objective of this research is to test how the influence of leadership style to job satisfaction. And to find the dominant leadership style in international Bank. To obtain this data ,Questiamains is used and spreading them to 54 respondent which are employees of International Bank. The method to analyze data is used Single Regression Analysis and Anova with Post Hoc Pairwise Multiple Comparisons. This research indicates that there is a relationship between leadership style and Job satisfaction. And the dominant leadership style in international Bank is task-oriented leadership style.Keywords: Leadership Style, Job Satisfaction